Neotethyan Ankara Melange, central Turkey: Formation by accretion of seamounts and supra-subduction zone ophiolites in an oceanic fore-arc setting - Robertson, Alastair H.F.; Parlak, Osman; Taslı, Kemal; Dumitrica, Paulian; Ustaömer, Timur (Journal of Asian Earth Sciences: X, 2023)
[Display omitted] •New field-based evidence and interpretation of a classic accretionary melange.•New sedimentary and structural evidence helps to elucidate melange genesis.•The Ankara Melange has some stratigraphical coherence and is not all chaotic.•New age data for siliceous and calcareous microfossils from the melange.•Collision of seamount & carbonate platform with oceanic fore arc (SSZ ophiolite). The Neotethyan Ankara Melange is a global reference for oceanic accretionary processes preserved in a collisional orogen. Here we show, based on eight representative outcrops around Ankara, that the melange encompasses stratigraphically coherent volcanic-sedimentary successions of mainly Late Jurassic-Early Cretaceous age. Our results indicate that the melange has a relatively organised tectonostratigraphy, in contrast to previous interpretations that emphasised its chaotic nature. Coherent volcanic-sedimentary successions of Late Jurassic-Early Cretaceous age are interpreted as flank facies of a large oceanic seamount (probably plume related) and its capping carbonate platform (atoll), including reef-and back-reef facies. Remnants of other seamounts are dated as Late Triassic-Early Jurassic and Late Cretaceous. Variably dismembered supra-subduction zone ophiolites of latest Early Jurassic-Middle Jurassic age, including boninites, formed in an oceanic fore-arc setting, similar to that of the Cenozoic Izu-Bonin fore arc, NW Pacific. The melange in the Ankara region partly accreted during the Early Cretaceous (pre-Albian) in response to collision of the inferred large seamount with the oceanic (ophiolitic) fore arc. During the collision which involved subduction-erosion slices of proximal–distal seamount flank lithologies accreted sequentially, whereas the seamount core subducted. Also during the collision, the distal outer edge of the ophiolitic fore arc, mainly mantle harzburgite, detached from the over-riding lithosphere and was incorporated into the melange. Structural evidence emphasises the importance of tectonic processes (rather than olistostromes) in the melange accretion. The accretionary prism in the outcrops studied was covered by arc-related sediments and volcanics during the Late Cretaceous and deformed by collision-related processes during latest Cretaceous-Paleogene.